Credit Card Practices, Attitudes, Problems And Risks Among Individuals: Empirical Findings Using Structural Equation Model - Mohamad Afzhan Khan Mohamad Khalil; Liana Mohamad; Ratna Khuzaimah Mohamad; Noral Hidayah Alwi; Loo Sin Chun, (Open University Malaysia (OUM), 2015)
Credit card unhealthy practices have been a world-wide challenge in the global business environment for years. The effect of default hits not only the victim, but also the banks, credit card companies and merchants. The objective of this paper is to examine the relationship amongst practices, attitudes, problems and risks related to credit card usage. A literature review on prior studies has indicated that there is a methodological gap to be filled in this area. Novelty is achieved by the usage of partial least square (PLS) model in answering the hypotheses. Multilevel method analysis using PLS allows for efficiency, convergence and power when investigating the causal effects in the two-level data, ensuring that the support for hypothesis is much more acceptable. Out of the 150 total survey questionnaires distributed, 114 were returned and used. Face to face data collection method was employed to enhance the response rate. Prior to collecting the data, the content of the survey questionnaire was reviewed by a content expert to enhance the understandability of the instrument. Mean analysis was performed to describe the profile of respondents. Mann Whitney test reports (p = 0.71) indicated that bias did not exist in this study, whereas Kolmogorov-Smirnov test in this paper showed (p > 0.05) proving normality in the data distribution. Convergent validity (average variance extracted > 0.50; composite reliability > 0.80) was also reported prior to presenting the final model. There is a relationship between problem, reason and risks related to credit card usage (p < 0.01). Missing bill payment due dates and paying the debts late could lead to many risks to the users. Poor financing habits can jeopardise relationships and can lead people to spend more than what is necessary. However, the relationship between the reason of using credit cards and the risk related to it is not significant (p = 0.13). Future researchers are suggested to include moderating and mediating factors in the structural equation model to narrow down the methodological gap available in this area. [ABSTRACT BY AUTHORS]